Electrophysiological and Behavioral Correlates of Global and Local Digits Processing. - Menashe, Shay; Mashal, Nira; Anaki, David (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2026)
The present study investigated global and local processing of hierarchical digits using a selective attention paradigm. Behavioural and event-related potentials measures were collected while participants performed global and local tasks in which hierarchical digits were presented to the centre of the screen. The first aim of this study was to investigate the global precedence effect. The second aim was to examine the lateralization patterns associated with global and local processing. The behavioural results indicated that the global precedence effect was not evident. In addition, the event-related potential findings showed that the global and local levels were processed in parallel during certain phases of processing, while different lateralization effects were found during processing. Although the N2 findings in the present study support the notion that this component is an index for global versus local processing even for hierarchical digits, the overall findings suggest that complex interactions between the hemispheres exist during the different phases of processing. The results are discussed in terms of the effects of both centrally presented hierarchical digits and the selective attention paradigm.